Study on the evaluation standard of extruded glutinous rice starch with thermostable α‐ amylase for making Chinese rice wine. (5th November 2021) - Guan, Zhongjing; Ren, Xiaoru; Bian, Shichao; Xu, Enbo; Jiao, Aiquan; Jin, Zhengyu
Summary: To promote the industrial production of Chinese rice wine made by enzymatic extrudates, the first is to ensure the consistency of the raw material. That is, an evaluation standard of enzymatic extrudate should be set up. It was studied for the first time. By studying the changes of seven indexes of samples at different sites of extruder barrel and the die along the extrusion direction and making the correlation analysis to select the representative indexes. The results showed that the change trends of dextrose equivalent (DE), molecular weight distribution (MWD) and oligosaccharide composition (OC) were the same, and these indexes were more affected by mechanical force than by temperature. The ability of degradation of different zones was: conveying area < kneading area << exit of the die. There was little difference in extent of gelatinisation (GE) at the temperature where the enzyme activity was relatively high. Different from DE value, water solubility index (WSI) rose gradually. Surprisingly, DE was negatively correlated with GE, and positively correlated with oligosaccharides except DP1 and DP6, and had no significant correlation with water absorption index (WAI) and WSI. In conclusion, DE, WSI, DPD (especially DP6) could be used as a comprehensive evaluation index of enzymatic extrudates. Abstract : The degradation degrees of starch were different with different screw configuration, temperature and pressure.